The Hepaticojejunostomy Technique with Intra-Anastomotic Stent in Biliary Diseases and Its Evolution throughout the Years: A Technical Analysis. (13th April 2016) - Moris, Demetrios; Papalampros, Alexandros; Vailas, Michail; Petrou, Athanasios; Kontos, Michael; Felekouras, Evangelos
Abstract : Roux-en-Y hepaticojejunostomy (RYHJ) is currently considered as the definitive treatment for iatrogenic bile duct injuries and the principal representative of biliary diversion procedures. This technique has met many milestones of extensive evolution, particularly the last years of concomitant technological evolution (laparoscopic/robotic approach). Anastomotic strictures and leaks, which may have deleterious effects on the survival and quality of life of a patient with biliary obstruction of any cause, made the need of the development of a safe and efficient RYHJ compulsory. The aim of this technical analysis and the juxtaposed discussions is to elucidate with the most important milestones and technical tips and tricks all aspects of a feasible and reliable RYHJ technique that is performed in our center for the last 25 years in around 400 patients.